Net share issues and the cross‐section of equity returns under a dividend imputation tax system. (6th May 2015) - Melia, Adrian; Docherty, Paul; Easton, Steve
Abstract: Despite considerable empirical evidence reporting a negative relationship between net share issuance and subsequent returns, it remains unresolved whether this anomaly is explained by risk or investor irrationality. This study examines the net share issuance anomaly using seasoned equity offerings before and after the introduction of an imputation tax system. We report robust evidence of a negative relationship between net share issuance and returns post‐imputation, but no relationship pre‐imputation. Our results provide evidence to support the international pervasiveness of the net share issuance anomaly, but more importantly suggest that this anomaly may be explained by risk.